Mitochondrial Retrograde Signaling Contributes to Metabolic Differentiation in Yeast Colonies - Plocek, Vítězslav; Fadrhonc, Kristýna; Maršíková, Jana; Váchová, Libuše; Pokorná, Alexandra; Hlaváček, Otakar; Wilkinson, Derek; Palková, Zdena (International journal of molecular sciences, 2021)
During development of yeast colonies, various cell subpopulations form, which differ in their properties and specifically localize within the structure. Three branches of mitochondrial retrograde (RTG) signaling play a role in colony development and differentiation, each of them activating the production of specific markers in different cell types. Here, aiming to identify proteins and processes controlled by the RTG pathway, we analyzed proteomes of individual cell subpopulations from colonies of strains, mutated in genes of the RTG pathway. Resulting data, along with microscopic analyses revealed that the RTG pathway predominantly regulates processes in U cells, long-lived cells with unique properties, which are localized in upper colony regions. Rtg proteins therein activate processes leading to amino acid biosynthesis, including transport of metabolic intermediates between compartments, but also repress expression of mitochondrial ribosome components, thus possibly contributing to reduced mitochondrial translation in U cells. The results reveal the RTG pathway's role in activating metabolic processes, important in U cell adaptation to altered nutritional conditions. They also point to the important role of Rtg regulators in repressing mitochondrial activity in U cells.
Keywords: analýza jednotlivých buněk; Repressor Proteins; Saccharomyces cerevisiae Proteins; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Mitochondria; proteom; represorové proteiny; Tandem Mass Spectrometry; Saccharomyces cerevisiae; Proteome; transkripční faktory BHLH-Zip; proteomika; Chromatography, Liquid; intracelulární signální peptidy a proteiny; signální transdukce; Signal Transduction; biosyntetické dráhy; mitochondrie; Proteomics; colony development and differentiation; tandemová hmotnostní spektrometrie; yeast colonies; Intracellular Signaling Peptides and Proteins; Gene Expression Regulation, Fungal; Biosynthetic Pathways; regulace genové exprese u hub; proteomic analysis; Amino Acids; Saccharomyces cerevisiae - proteiny; aminokyseliny; Single-Cell Analysis; mitochondrial retrograde signaling; chromatografie kapalinová